2016
DOI: 10.1038/nature18938
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis of potent Zika–dengue virus antibody cross-neutralization

Abstract: Zika virus (ZIKV) is an arthropod-borne enveloped virus belonging to the Flavivirus genus in the family Flaviviridae, which also includes the human pathogenic yellow fever, dengue, West Nile and tick-borne encephalitis viruses 1 . Flaviviruses have two structural glycoproteins, prM and E (for precursor membrane and envelope proteins, respectively), which form a heterodimer in the endoplasmic reticulum (ER) of the infected cell and drive the budding of spiky immature virions into the ER lumen. These particles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
540
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(578 citation statements)
references
References 44 publications
(49 reference statements)
19
540
0
3
Order By: Relevance
“…Interestingly, the FLE is highly conserved between DENVs and ZIKV and anti-FLE produced from DENV infected patients can bind with high affinity to monomeric ZIKV E-protein 21,22 . However, these anti-FLE mAb fail to neutralize ZIKV infection but promote ADE, which is consistent with the concept that ZIKV is more rigid than the DENVs thereby limiting access to the FLE 16,21,23 .…”
Section: The Immunodominant Fusion Loop Epitopesupporting
confidence: 65%
See 2 more Smart Citations
“…Interestingly, the FLE is highly conserved between DENVs and ZIKV and anti-FLE produced from DENV infected patients can bind with high affinity to monomeric ZIKV E-protein 21,22 . However, these anti-FLE mAb fail to neutralize ZIKV infection but promote ADE, which is consistent with the concept that ZIKV is more rigid than the DENVs thereby limiting access to the FLE 16,21,23 .…”
Section: The Immunodominant Fusion Loop Epitopesupporting
confidence: 65%
“…Crystal structures of EDE1 antibodies binding to the ZIKV envelope dimer reveal the strong conservation of this epitope between ZIKV and DENV 23 .…”
Section: Dengue and Zika Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, such as influenza virus (Kanekiyo et al , 2013; Krammer & Palese, 2014; Yassine et al , 2015) or human immunodeficiency virus (HIV) (Kwong et al , 2013), a universal vaccine is sought to overcome strain variability so that a single immunogen designed to reorient the antibody response toward relatively conserved antigenic regions would protect against infections with highly divergent antigenic variants. In other cases, the aim is to develop vaccines that will cross‐protect against related viruses from the same family, such as the Flaviviridae Zika and dengue viruses (Barba‐Spaeth et al , 2016). Beyond viruses, universal vaccines are also being designed for Neisseria meningitidis with chimeric variants of the factor H binding protein that incorporate epitopes of highly divergent bacterial strains (Scarselli et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…E protein is a glycoprotein responsible for virus entry, representing a major target of neutralizing antibodies for Flaviviruses, including Zika virus, Dengue virus, and other mosquito-transmitted viruses from the same family, was shown to bind to DC-SIGN via the glycans on E proteins of the mature virion [70]. It has been already demonstrated that broadly neutralizing antibodies for E-dimer epitope isolated from patients with Dengue disease neutralize Zika as potently as they neutralize Dengue virus [71] E protein of Zika virus differs from the other known Flaviviruses in the ~10 amino acids that surround the Asn154 glycosylation site in the virus shell [68]. The virus projects a glycosylation site outward and glycans are attached to the viral protein surface at this site.…”
Section: Zika Virusmentioning
confidence: 99%